2017
DOI: 10.1080/02656736.2017.1371342
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nutritional risk assessment in patients undergoing cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy for colorectal carcinomatosis

Abstract: Hypoalbuminemia appears as a strong predictive factor for decreased overall survival in patients presenting PM of colorectal origin undergoing CRS-HIPEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 24 publications
3
31
1
3
Order By: Relevance
“…PCI has been one of the most consistent independent predictors of morbidity and mortality from CRS-HIPEC. 2,[5][6][7][8][9] There has, however, been no consensus on a PCI cut off in CPM that predicts poorer post-operative outcomes, with studies thus far reporting a wide range (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) that are significantly predictive of DFS and OS. 6,8,[10][11][12] Results from our study suggest that for patients with PC from colorectal primaries, a lower cut-off value of 7-11 is a satisfactorily significant predictor of postoperative OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCI has been one of the most consistent independent predictors of morbidity and mortality from CRS-HIPEC. 2,[5][6][7][8][9] There has, however, been no consensus on a PCI cut off in CPM that predicts poorer post-operative outcomes, with studies thus far reporting a wide range (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) that are significantly predictive of DFS and OS. 6,8,[10][11][12] Results from our study suggest that for patients with PC from colorectal primaries, a lower cut-off value of 7-11 is a satisfactorily significant predictor of postoperative OS.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies on this topic have reported on the predictive value of DFI between repeated CRS-HIPEC for higher PCI, CC score and poorer long-term survival. 9,10,13,14 Our study is one of the few to define DFI as the interval between index curative surgery and first metachronous peritoneal recurrence for which the patient underwent CRS-HIPEC. A longer DFI is a surrogate marker of favourable tumour biology, and allows optimization of nutritional and functional status preoperatively, a factor reported to be significantly associated with post-CRS-HIPEC OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of enteral nutrition should be considered in all patients before surgery particularly those who are malnourished (albumin <30) to reduce morbidity and mortality [17].…”
Section: Preoperative Preparationmentioning
confidence: 99%
“…Verwaal et al [4] demonstrated in a randomised trial that CRS and HIPEC offers an improved survival of 22.3 months compared to 12.6 months with systemic chemotherapy only in the management of colorectal peritoneal metastases. Since then, a number of other studies have reported favourable median survival of 30-58 months with CRS and HIPEC, with a 27-46% 5-year survival [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%